A Quantitative Study of History in the English Short-Title Catalogue (ESTC), 1470-1800 - Lahti, Leo; Ilomäki, Niko; Tolonen, Mikko (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2015)
This article analyses the publication trends of history in early modern Britain and North-America, 1470-1800, based on the English Short-Title Catalogue (ESTC) data. Its most important contribution is a demonstration how digitized library catalogues can become a crucial tool for scholarship and part of reproducible research. The article also suggests a novel way how to make a quantitative analysis of a particular trend in book production, namely publishing of history. This study is also our first experiment with the analysis of paper consumption in early modern book production. It demonstrates in practice the importance of open science principles for library and information science. The article studies three main research questions: 1) who wrote history 2) where was history published, and 3) how did publishing of history change over time in early modern Britain and North America. As the main findings, we demonstrate that the average book size for history publications becomes smaller over time and that the octavo-sized book is the rising vehicle of history in the eighteenth century that tells us factually about widening audiences. The article will also compare different aspects of most popular authors on history such as Edmund Burke and David Hume. While focusing on history publishing, these findings may reflect more widespread trends in publication in the early modern era, and this article illustrates how some of the key questions in this field can be assessed by statistical analysis of large-scale bibliographic data collections.